2012
DOI: 10.5121/ijdps.2012.3130
|View full text |Cite
|
Sign up to set email alerts
|

Design of Wireless Electronic Stethoscope Based on Zigbee

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Based on the results obtained in Figures 11 and 12, it has been shown that with the combination of Butterworth LPF and HPF filters, got significant results to show the regular signal pattern in a Figure 1 pattern when compared to using only one filter that is only Butterworth LPF [19]- [20], the results are still far from the expected normal pattern according to Figure 1. Figure 11.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results obtained in Figures 11 and 12, it has been shown that with the combination of Butterworth LPF and HPF filters, got significant results to show the regular signal pattern in a Figure 1 pattern when compared to using only one filter that is only Butterworth LPF [19]- [20], the results are still far from the expected normal pattern according to Figure 1. Figure 11.…”
Section: Methodsmentioning
confidence: 99%
“…(Gururajan et al 2011) conducted a study based on different de-signs of wireless electronic stethoscopes and their feasibility based on user's perspective to identify issues when using these stethoscopes in telemedicine and e-health platforms [6]. (Patil, et al 2012) proposed the design of contact vibration sensor to minimize the ambient noise in acquiring the heart sound signal, for wireless transmission the authors used Bluetooth for ehealthcare implementation [2]. (Wang et-al ,2009)proposed the heart sound measurement and analysis system with digital stethoscope, this paper is concerned with the cardiac sound measurement and analysis system for in-home use of heart abnormality monitoring [8][9].…”
Section: Related Workmentioning
confidence: 99%
“…Murmurs are eliminated using 'Low pass Butterworth filter' & wirelessly transmitted using RF module. Power amplifier is used for driving signals which could be heard by headphones or stored in MP3 player for further analysis [2].…”
Section: Proposed Wireless Stethoscope Using Butterworth Filtermentioning
confidence: 99%
“…Through a review of previous researches which are summarized in Table 2, obviously, most of them supported the ZigBee wireless standard for bicycle monitoring. This protocol was most often selected as the wireless transmission technology because of its low cost [69], low power consumption [70,71], higher network elasticity, a large number of nodes [72], greater coverage area, and secure networking [73]. Bluetooth is embedded in most portable mobile phones and computers [74] and has low cost, low EM interference [75], low-power applications [76], and low complexity [77], but it has appeared in few works considered in this study.…”
Section: Advantagesmentioning
confidence: 99%